PROGNOSTIC SCORES FOR CARDIOVASCULAR DISEASES - F. I. Belyalov (SINAPS LLC, 2015)
The prognostic scores for cardiovascular diseases are discussed in this article. The scores have advantages and limitations for using in clinical practice. Author has developed the program CardioExpert for mobile devices including the most essential scores for cardiovascular diseases.